ASPEK EKOLOGI DAN PERTUMBUHAN KERANG BULU (Anadara antiquata) DI PERAIRAN LETMAN, KABUPATEN MALUKU TENGGARA - Rosita Silaban; Dortje Thedora Silubun; Ahmad Ade Rifandi Jamlean (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2021)
ABSTRACTFeather shells are an important commodity that has the potential to be developed. Feather shells are a fishery resource that has been exploited for thousands of years for consumption. The objectives of this study were 1) to examine individual density, 2) relative density, 3) distribution pattern, 4) relationship of length and weight and 5) condition factors of feather shells. Sampling was carried out using the belt transect method. The sample of feather shells was then measured for the length, width and height of the body and weighed. Based on the transect, the individual density of feather clams (Anadara antiquata) was found on transect 4, which was 0.338 ind / m2, while the lowest density was found on transect 2, which was 0.05 ind / m2. The highest relative density of feather shells was on transect 4 at 19% and the lowest was on transects 1 and 2 at 1%. The distribution of feather shells was obtained that the feather shells had a clustered distribution pattern with an Id value of 1.30 (Id 1). The correlation between length and weight of feather shells was found to have a b value of 2.60 so that the growth pattern was classified as positive allometric (b 2.50). The condition factor obtained an average value of 1.25 indicating that the environmental conditions were good enough for the organism (Kn 1).Keywords: feather shells, ecological aspects, growth, LetmanABSTRAKKerang bulu merupakan salah satu komoditas penting yang sangat potensial dikembangkan. Kerang bulu menjadi salah satu sumber daya perikanan yang telah dieksploitasi sejak beribu-ribu tahun yang lalu untuk dikonsumsi. Tujuan dari penelitian ini yaitu 1) mengkaji kepadatan individu, 2) kepadatan relatif, 3) pola distribusi, 4) hubungan panjang dan berat serta 5) faktor kondisi kerang bulu. Pengambilan sampel dilakukan dengan menggunakan metode belt transek. Sampel kerang bulu kemudian dilakukan pengukuran panjang, lebar dan tinggi tubuh serta ditimbang beratnya. Kepadatan individu kerang bulu (Anadara antiquata) berdasarkan transek diperoleh kepadatan tertinggi terdapat pada transek 4 yaitu sebesar 0,338 ind/m2 sedangkan kepadatan terendah terdapat pada transek 2 yaitu sebesar 0,05 ind/m2. Kepadatan relatif tertinggi kerang bulu terdapat pada transek 4 sebesar 19% dan terendah pada transek 1 dan 2 sebesar 1%. Distribusi kerang bulu diperoleh kerang bulu memiliki pola penyebaran mengelompok dengan nilai Id sebesar 1,30 (Id1). Hubungan panjang dan berat kerang bulu didapati nilai b sebesar 2.60 sehingga pola pertumbuhan tergolong allometrik positif (b2.50). Faktor kondisi diperoleh nilai rata-rata sebesar 1.25 menunjukan kondisi lingkungan cukup baik bagi organisme (Kn1).Kata kunci: kerang bulu, aspek ekologi, pertumbuhan, Letman